Pembinaan Nilai Tambah dan Pendapatan Melalui Tanaman Hidroponik di Desa Kalijati Kecamatan Jatisari Kabupaten Karawang - Wawan, Wawan; sah, Adrian; Fadillah, Rijal Muhammad (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
In the Kalijati village there are still many young people who have free time that can be used for activities that provide added value for the neighborhood and economic value. Whereas there are still many business opportunities to increase income that can be done by residents but are not used by one of them the availability of land around the house for hydroponic plants. The stages or steps taken in this service activity, namely the approach and participation of the community there are providing education about the importance of becoming entrepreneurs, hydroponic business management, hydroponic planting practices, advertising and promotion and related selling prices. The results show that the community is increasingly understanding about the importance of entrepreneurship, making hydroponic plants, how to advertise it and how to calculate the selling price simply